1985
DOI: 10.1115/1.3239796
|View full text |Cite
|
Sign up to set email alerts
|

Application of Reburning for NOx Control to a Firetube Package Boiler

Abstract: A 730 kW (2.5 × 106 Btu/hr) firetube package boiler was used to demonstrate the application of reburning for NOx emission control. An overall reduction of 50 percent from an uncontrolled NOx emission of 200 ppm was realized by diverting 15 percent of the total boiler load to a natural-gas-fired second stage burner. Tests indicate that the overall reaction order of destruction with respect to initial NOx is greater than one; thus, larger reductions can be expected from reburning applications to systems with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1988
1988
1998
1998

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Other studies (Kelly et al, 1986;Lanier et al, 1986; showed no clear optimum as the reburn zone stoichiometry decreased. The results of Lanier et al (1986), Mulholland and Lanier (1985) and Mulholland and Hall (1986) in a package boiler simulator suggest that an optimum reburning effectiveness might be obtained at reburn zone stoichiometries below . 0.7.…”
Section: Rebum Zon¢_stoichiometry_mentioning
confidence: 96%
“…Other studies (Kelly et al, 1986;Lanier et al, 1986; showed no clear optimum as the reburn zone stoichiometry decreased. The results of Lanier et al (1986), Mulholland and Lanier (1985) and Mulholland and Hall (1986) in a package boiler simulator suggest that an optimum reburning effectiveness might be obtained at reburn zone stoichiometries below . 0.7.…”
Section: Rebum Zon¢_stoichiometry_mentioning
confidence: 96%
“…To illustrate the scope of issues involved, a brief review of several recent investigations is given. Ishikawajima-Harma (1983, Mulholland andHall (1985) and Mulholland and Lanier (1985) of AcurexEPA, Greene, McCarthy, and Overmoe from EER (1985), and Mulholland and Hall of AcurexEPA (1987). This research yielded slightly different results as to the applicability of different fossil hels as a reburn fuel.…”
Section: -3mentioning
confidence: 99%
“…However the reburning concept accomplishing fifty percent NO removal was reported only in 1983, when x Takahashi et al (1983) reported results using natural gas as a reburning fuel. Mulholland and Lanier (1984) studied NO control by reburning in a firetube package boiler. Energy and x Environment Research Corporation (Greene and Weaver, 1974;Overmoe et al 1986), and U.S. Environmental Protection Agency (Mulholland and Hall.…”
Section: Current Reburning Research Projectsmentioning
confidence: 99%